Experimental and numerical analysis of hydrodynamic impact on stiffened side of three-dimensional elastic stiffened plates - Hua Sun (Advances in Mechanical Engineering, 2018)
Hydroelasticity is a phenomenon which occurs during the interaction between water and a deformable structure. Predicting the structural deformation and stress during water entry is a highly challenging endeavor and suitable computer-aided design tools are currently being developed and validated. This article discusses a hydrodynamic problem of the water impact on the stiffened side of elastic stiffened plates; the problem is addressed via an experimental approach and by explicit finite element method with a Multi-Material Arbitrary Lagrangian–Eulerian solver. A series of water entry tests were conducted to measure the impact pressure and effective stress on the stiffened panel at different drop heights. Convergence studies were conducted to run the numerical analysis; the results are consistent with the experimental data. Influences of drop height, stiffeners, and air cushion on pressure and effective stresses are discussed. Impact pressure and effective stress increase linearly with drop height. Stiffeners with different dimensions and directions appear to exert various effects on the maximum value, duration, and starting time of pressure and stress. The air cushion primarily increases the pressure duration and reduces its maximum value, and its property is discussed in detail.